Actors in real estate production and housing typology in greater Abidjan in Ivory coast - Deki, Kouakou Tehua Pierre; Zinsou-Klassou, Kossiwa; Bénoît, Danvide T. (Edelweiss Applied Science and Technology, 2025)
Urbanization in Africa generates a strong demand for housing from the population. Greater Abidjan is not exempt from this situation. This urban growth is creating a significant demand for housing in the city. In response to this situation, the State and private developers are making efforts to provide the population with housing. The objective of this article is to study land and housing production in Greater Abidjan. Through a methodology that combines qualitative and quantitative aspects, we have arrived at results indicating that land production in the study area is controlled by the State, which also participates in the construction of housing. In addition to the State, private companies are involved in housing production. The housing produced is essentially of three types: very economical, economical, and of good standing.